{5,10,15,20-Tetrakis[4-(octyloxy)phenyl]porphyrinato}copper(II) - Yang, De-Liang (International Union of Crystallography, 2011)
In the title compound, [Cu(C(76)H(92)N(4)O(4))], the central Cu(II) ion is situated on an inversion centre. The porphyrinate core exhibits a nearly planar conformation [maximum deviation = 0.027 (3) Å], with Cu—N distances of 1.997 (2) and 2.001 (2) Å. The benzene rings of the 4-octyloxyphenyl groups are rotated at angles of 84.02 (8) and 77.02 (6)° with respect to the mean plane of the porphyrin fragment. The two terminal C atoms in the octyl group are disordered over two positions of equal occupancy.